Occurrence, distribution, and bioaccumulation of new and legacy persistent organic pollutants in an ecosystem on King George Island, maritime Antarctica - Kim, Jun-Tae; Choi, Yun-Jeong; Barghi, Mandana; Kim, Jeong-Hoon; Jung, Jin-Woo; Kim, Kitae; Kang, Jung-Ho; Lammel, Gerhard; Chang, Yoon-Seok (Journal of hazardous materials, 2021)
The occurrence and bioaccumulation of new and legacy persistent organic pollutants (POPs), organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs), polychlorinated naphthalenes (PCNs), hexabromocyclododecanes (HBCDs), and Dechlorane Plus (DPs) and their related compounds (Dechloranes) in an ecosystem on King George Island, Antarctica are investigated. The new and legacy POPs were widely detected in the animal samples collected from Antarctica, which included Limpet, Antarctic cod, Amphipods, Antarctic icefish, Gentoo and Chinstrap penguins, Kelp gull, and South polar skua. The trophic magnification factors indicated that the levels of PCNs and HBCDs, as well as the legacy POPs, were magnified through the food web, whereas DPs might be diluted through the trophic levels contradicting the classification of Dechloranes as POPs. This is one of the first extensive surveys on PCNs, HBCDs, and Dechloranes, which provides unique information on the distribution and trophic biomagnification potential of the new and legacy POPs in the Antarctic region.
Keywords: monitorování životního prostředí; Trophic magnification factor; ekosystém; polychlorované bifenyly; Persistent Organic Pollutants; Environmental Monitoring; Bioaccumulation; chemické látky znečišťující vodu; Antarctic Regions; Animals; Polychlorinated Biphenyls; Polychlorinated naphthalenes; Water Pollutants, Chemical; zvířata; perzistentní organické znečišťující látky; Hexabromocyclododecane; Persistent organic pollutants; Antarktida; Ecosystem; bioakumulace; Dechloranes